Study of knowledge about Science Fair in the Minutes of ENPEC and REDALYC: significant aspects to the process of teaching and learning in High School (Research, Society and Development, 2020)
This article aims to analyze significant aspects with the Science Fairs event, in public schools in the city of Alto Alegre, Roraima (RR), from the perspective of high school students and teachers. We sought to answer the problem: What are the significant aspects with the Science Fairs event, in public schools in the city of Alto Alegre (RR), from the perspective of high school teachers and students? The methodology is exploratory, qualitative and quantitative, therefore, mixed; a bibliographic analysis was also carried out. The search was based on the following databases: Proceedings of the National Research Meeting in Science Education (ENPEC), Redalyc Red Scientific Information System of Latin American and Caribbean Scientific Journals (REDALYC). As a result, we observed that when the uniterms are placed separately in the thematic area, many articles appear. However, when the filtering starts, the  number of articles decreases significantly whereas, when the four uniterms are added, related articles appear in only one of the researched bases. In this sense, there are few productions on the subject and therefore we emphasize the importance of developing research on Science Fair events in schools, considering the teaching and learning process of students.